Algicidal lactones from the marine Roseobacter clade bacterium Ruegeria pomeroyi - Riclea, Ramona; Gleitzmann, Julia; Bruns, Hilke; Junker, Corina; Schulz, Barbara; Dickschat, Jeroen S. (Beilstein Journal of Organic Chemistry, 2012)
Volatiles released by the marine Roseobacter clade bacterium Rugeria pomeroyi were collected by use of a closed-loop stripping headspace apparatus (CLSA) and analysed by GC–MS. Several lactones were found for which structural proposals were derived from their mass spectra and unambiguously verified by the synthesis of reference compounds. An enantioselective synthesis of two exemplary lactones was performed to establish the enantiomeric compositions of the natural products by enantioselective GC–MS analyses. The lactones were subjected to biotests to investigate their activity against several bacteria, fungi, and algae. A specific algicidal activity was observed that may be important in the interaction between the bacteria and their algal hosts in fading algal blooms.
Keywords: bacteria-algae symbiosis; lactones; Roseobacter; synthesis; volatiles